“Close to the tip, with little bone to grip”: stabilizing two periprosthetic proximal femur fractures above a distal femur megaprosthesis using a combination of DHS and 3.5 mm screws - José-Vicente Andrés-Peiró; Carlos Alberto Piedra-Calle; Jordi Tomàs-Hernández; Pablo S. Corona; Carles Amat; Jordi Teixidor-Serra (Trauma Case Reports)
The incidence of periprosthetic fractures is increasing, presenting significant challenges due to patient longevity and the complexity of repeated surgeries. This report details the successful treatment of a previously unreported periprosthetic fracture pattern using a modified dynamic hip screw (DHS) technique. Two cases involved patients with extracapsular fractures in short proximal femur segments above megaprostheses. The fractures were reduced and stabilized with a DHS device, complemented by 3.5 mm screws from a different manufacturer to achieve effective bicortical fixation around the thick stems. Early weight-bearing was initiated postoperatively, with both patients achieving fracture healing without mechanical complications. This approach highlights the importance of careful preoperative planning and the selection of appropriate fixation methods, particularly in complex cases where traditional solutions may not be viable.